Parathyroid Changes After RAI in Patients With Differentiated Thyroid Carcinoma - Xiao, Liu; Zhang, Wenjie; Zhu, Hongmei; Wang, Yueqi; Liu, Bin; Huang, Rui; Li, Lin (Frontiers in Endocrinology, 2021)
Objective: The purpose of this study was to investigate parathyroid hormone (PTH), serum calcium, phosphorus, and 25-hydroxyvitamin D (25-OH-VD) changes before and after radioactive iodine (RAI) in differentiated thyroid carcinoma (DTC) patients at different time points. Methods: A total of 259 DTC patients who received RAI were prospectively enrolled. We evaluated PTH, serum calcium, phosphorus, and 25-OH-VD levels at baseline pre-RAI, five days, six weeks, and six months post-RAI, respectively. We analyzed the risk factors of hypocalcemia at five days post-RAI. Results: The mean PTH, serum calcium and phosphorus values decreased five days post-RAI compared with pre-RAI (PTH 4.18 ± 1.23 pmol/L vs. 3.95 ± 1.41 pmol/L; calcium 2.27 ± 0.09 mmol/L vs. 2.20 ± 0.11 mmol/L; phosphorus 1.25 ± 0.17 vs. 0.98 ± 0.20 mmol/L, P < 0.05), and the differences were statistically significant. The mean 25-OH-VD levels did not significantly decrease at five days post-RAI. 21.2% (55/259) of patients had hypocalcemia at five days post-RAI, and all of them were given oral calcium supplements. At six weeks post-RAI, all of the above parameters were higher than those at five days post-RAI. Multivariate regression analysis showed that baseline pre-RAI serum calcium < 2.27 mmol/L, PTH < 4.18 pmol/L and negative 99mTcO4- thyroid imaging were risk factors for hypocalcemia at five days post-RAI. Conclusion: For DTC patients with normal PTH and serum calcium levels at pre-RAI, their PTH, serum calcium, and phosphorus levels decreased at five days post-RAI. About one-fifth of patients could have hypocalcemia at five days post-RAI. Lower baseline pre-RAI serum calcium and PTH levels and negative 99mTcO4- thyroid imaging were risk factors for hypocalcemia five days post-RAI.